Knowledge Creation and Performance of Private Health Facilities in Kisii County, Kenya - Manyange Abuki, Alice; Muchemi, Anne W. (International Journal of Scientific Research and Management (IJSRM), 2022)
Well performing private health facilities afford countries access to quality healthcare and support services, easing the disease burden in public health facilities. Being a knowledge-driven industry, the field of medicine keeps advancing, highlighted by new discoveries in treatments from continuing research. As such, desirable performance among private health facilities would ideally necessitate that healthcare providers adequately share knowledge. By so doing, when one that bears knowledge that is specialized exists the facility, other staffs may continue accessing the knowledge, thus decreasing the probability of committing errors as a result of misinformation. Whereas extant studies attempt to link knowledge sharing and organizational performance, their focus has been on industries other than private healthcare. The present research thus set out to assess the effect of knowledge sharing on the performance of private health facilities in Kisii County, Kenya. The study was grounded on both knowledge-based view, and upper echelon theories. The research adopted both descriptive and explanatory research designs, with the target population comprising 135 staff drawn from all 43 private health entities in Kisii County. The research used a census survey with one top cadre staff from each facility forming the unit of observation. The research involved the gathering of data that is primary by utilizing a questionnaire that is semi-structured. Inferential and descriptive calculations were then computed in data analysis. Findings reveal a statistically significant relationship between knowledge sharing (β = .221, Sig.=.008